(untitled) (American Journal of Human Psychology, 2024)
This quantitative research study investigates the relationship between personality traits and happiness of 291 University Students in Region XI (Davao Region) and Region XII (SOCCSKSARGEN), Philippines. The respondents of this research were chosen using stratified random sampling. Two reliable and validated questionnaires were used to extract data from the university students. Based on the notable findings of the study, agreeableness, and extraversion have a significant positive relationship with happiness, with respective beta coefficients of 0.282 and 0.347, respectively. On the other hand, neuroticism has a negative significant relationship with happiness, with a beta coefficient of -0.264. Subsequently, conscientiousness and openness to experience have no significant relationship with happiness. The study offers significant and fresh data about the happiness index of university students in two different regions of the peninsula.